Relation of backpack weight with Low Back Pain (LBP) Complaints in students of SMP - Heni Fa'riatul Aeni; Herlinawati Herlinawati; Cucu Herawati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Abstract Background: Using a backpack with a load that weighs â‰¥ 10% of body weight can cause Low Back Pain (LBP) complaint. This study aims to determine the relationship between backpack weight and low back pain (LBP) complaints among students of State JHS 1 Talun, Cirebon Regency. Method: This was a descriptive quantitative study with cross sectional design. The data were collected using several methods. Backpack weight was measured using a scale and low back pain (LBP) complaints were collected by means of interviews. The population of this study were all 813 students of State JHS 1 Talun Cirebon Regency in 2019, with a sample number of 89 taken using a proportional random sampling technique. Analysis of the data in this study was conducted through the Chi-Square statistical test. Results: There was a relationship between backpack weight and low back pain (LBP) complaints among students of State JHS 1 Talun, Cirebon Regency in 2019 with a P value = 0.008. Conclusion: Using a backpack with a heavy load can cause low back pain (LBP) complaints. Keywords: Backpack weight, Low back pain